The Condition of Climate Change Adaptation in Polish Municipalities Before and After the Pandemic on the Basis of Cso Environmental Indicators - Management Implications - Śmietanka, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The pandemic undoubtedly had a significant impact on local development management processes in municipalities in economic, social, environmental and institutional-political dimensions. The article presents and evaluates various activities of municipal governments in the field of environmental management for climate protection and formulates recommendations for municipalities in this regard.
Keywords: climate change adaptation; municipality; COVID-19; pandemic; governance